Association of genetic mutations in Plasmodium vivax dhfr with resistance to sulfadoxine-pyrimethamine: geographical and clinical correlates. - Imwong, M; Pukrittakayamee, S; Looareesuwan, S; Pasvol, G; Poirreiz, J; White, N; Snounou, G (2001)
Mutations in the Plasmodium falciparum gene (dhfr) encoding dihydrofolate reductase are associated with resistance to antifols. Plasmodium vivax, the more prevalent malaria parasite in Asia and the Americas, is considered antifol resistant. Functional polymorphisms in the dhfr gene of P. vivax (pvdhfr) were assessed by PCR-restriction fragment length polymorphism using blood samples taken from 125 patients with acute vivax malaria from three widely separated locations, Thailand (n = 100), India (n = 16), and Madagascar and the Comoros Islands (n = 9). Upon evaluation of the three important codons (encoding residues 57, 58, and 117) of P. vivax dhfr (pvdhfr), double- or triple-mutation genotypes were found in all but one case from Thailand (99%), in only three cases from India (19%) and in no cases from Madagascar or the Comoros Islands (P < 0.0001). The dhfr PCR products of P. vivax from 32 Thai patients treated with the antifolate sulfadoxine-pyrimethamine (S-P) were investigated. All samples showed either double (53%) or triple (47%) mutations. Following treatment, 34% of the patients had early treatment failures and only 10 (31%) of the patients cleared their parasitemias for 28 days. There were no significant differences in cure rates, but parasite reduction ratios at 48 h were significantly lower for patients whose samples showed triple mutations than for those whose samples showed double mutations (P = 0.01). The three mutations at the pvdhfr codons for residues 57, 58, and 117 are associated with high levels of S-P resistance in P. vivax. These mutations presumably arose from selection pressure.